Study of redshifted H I from the epoch of reionization with drift scan - Paul, S.; Sethi, S.; Subrahmanyan, R.; Udaya Shankar, N.; Dwarakanath, K.; Deshpande, A.; Bernardi, G.; Bowman, J.; Briggs, F.; Cappallo, R.; Corey, B.; Emrich, David; et al. (Institute of Physics Publishing, 2014)
The detection of the Epoch of Reionization (EoR) in the redshifted 21-cm line is a challenging task. Here we formulate the detection of the EoR signal using the drift scan strategy. This method potentially has better instrumental stability as compared to the case where a single patch of sky is tracked. We demonstrate that the correlation time between measured visibilities could extend up to 1-2 hr for an interferometer array such as the Murchison Widefield Array (MWA), which has a wide primary beam. We estimate the EoR power based on cross-correlation of visibilities across time and show that the drift scan strategy is capable of the detection of the EoR signal with comparable/better signal-to-noise as compared to the tracking case. We also estimate the visibility correlation for a set of bright point sources and argue that the statistical inhomogeneity of bright point sources might allow their separation from the EoR signal.